Construct Validity of the Multidimensional Scale of Perceived Social Support among Indonesian Mothers of Children with Autoimmune Conditions - Rosita Yuniati; Setiasih; Andrian Pramadi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Social support is a multidimensional construct that is central to the psychological well-being of caregivers facing sustained caregiving responsibilities. Despite its importance, empirical evidence supporting the psychometric validity of the Multidimensional Scale of Perceived Social Support (MSPSS) among caregiver populations in Indonesia remains limited, particularly among mothers caring for children with autoimmune diseases. This study aimed to evaluate the construct validity of the MSPSS within this specific caregiving context. A quantitative psychometric approach was employed, involving 399 Indonesian mothers recruited from hospitals and autoimmune support communities. Confirmatory Factor Analysis (CFA) was conducted to assess the hypothesized three dimensions of perceived social support, namely family, friends, and significant others. The results demonstrated satisfactory model fit (CFI = 0.947; TLI = 0.932; RMSEA = 0.068; SRMR = 0.039). Convergent validity was supported by adequate indicator loadings, Average Variance Extracted values ≥ 0.50, and Composite Reliability coefficients exceeding 0.70. These findings confirm that the MSPSS demonstrates robust construct validity and reliability for assessing perceived social support among Indonesian caregiver mothers, supporting its use in both research and clinical settings. Keywords: construct validity, social support, confirmatory factor analysis, caregivers, autoimmune disease